Russian Federation Contribution to Cutting Greenhouse Gas Emissions: Regulating Mechanisms and Advanced Technological Solution of their Implementation - V. V. Brizhanin; R. V. Filippova; E. V. Sudarikova; M. D. Sudarikov (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The issue of growth in greenhouse emissions to the atmosphere is the most principle challenge of our century. Adverse after-effects of climate change require harmonization of global tasks dealing with climate protection and human activity. The article grounds the necessity to cut greenhouse gas emissions and shows our possibilities in this field. The authors study and analyze legislative initiatives and economic tools of the low-carbon development in Russia. The article shows risks for sustainable development of national economy, which are feasible in case climate agenda is ignored. It was proved that introduction of obligatory reporting on greenhouse emissions and business urge towards standards in three categories ESG – assessment (social, managerial and ecological) can directly impact eco-innovation development, green technologies and motivate home organizations to introduce such innovation. The authors put forward a technological solution on system intensification of search, working-out and introduction of eco-innovation aimed at lowering the amount of greenhouse emissions to home industry. The proposed digital service on devising and introducing scientific and technological projects and ecological technologies could cut enterprises’ pay for greenhouse gas quotas and later increase proceeds of commercial work. Finally, conclusions were made that in Russia necessary conditions were created for development and introduction into industry technological solutions, which possess positive social, ecological and economic effects for enterprise upgrading and cutting greenhouse gas emissions.